Multilingualism across the Lifespan - Røyneland, Unn; Blackwood, Robert (Routledge Critical Studies in Multilingualism, 2022)
This innovative collection examines key questions on language diversity and multilingualism running through contemporary debates in psycholinguistics and sociolinguistics. Reinforcing interdisciplinary conversations on these themes, each chapter is co-authored by two different researchers, often those who have not written together before. The combined effect is a volume showcasing unique and dynamic perspectives on such topics as multilingualism across the lifespan, bilingual acquisition, family language policy, language and ageing, language shift, language and identity, and multilingualism and language impairment. The book builds on Elizabeth Lanza's pioneering work on multilingualism across the lifespan, bringing together cutting-edge research exploring multilingualism as an evolving phenomenon at landmarks in individuals', families', and communities' lives.　Taken together, the book offers a rich portrait of the different facets of multilingualism as a lived reality for individuals, families, and communities. This ground-breaking volume will be of particular interest to students and scholars in multilingualism, applied linguistics, sociolinguistics, and psycholinguistics.